Mekanika Gerakan dalam Cabang Olahraga Renang Gaya Dada (Lembaga Pengembangan Kinerja Dosen, 2026)
Breaststroke is one of the most widely used swimming styles, requiring coordination of hand, leg, and breathing movements to produce effective and efficient movement in the water. This study aims to analyze the mechanics of breaststroke movements to understand how these movements can improve swimming performance. The research method was conducted through literature study and technical observation of breaststroke movements. The results show that proper coordination of hand and leg movements and correct breathing techniques are the keys to success in breaststroke swimming. Conclusions and suggestions are also provided for the development of optimal techniques in breaststroke swimming.